Citrate dialysate does not induce oxidative stress or inflammation in vitro as compared to acetate dialysate - Pérez-García, Rafael; Ramírez Chamond, Rafael; de Sequera Ortiz, Patricia; Albalate, Marta; Puerta Carretero, Marta; Ortega, Mayra; Ruiz Caro, M Caridad; Alcazar Arroyo, Roberto (Nefrologia : publicacion oficial de la Sociedad Espanola Nefrologia, 2017)
Increased acetataemia during haemodialysis sessions has been associated with a number of abnormalities, including increased oxidative stress, pro-inflammatory cytokines and nitric oxide synthesis. However, citric acid may play an alternative role to acetate as a dialysate stabiliser given that the effect of citrate on complement and leukocyte activation is different to that of acetate. The purpose of this study was to compare the inflammatory effect in immunocompetent blood cells of acetate dialysate and citrate dialysate. The effect of acetate and/or citrate was investigated in the whole blood of uraemic patients and in healthy in vitro samples. Four types of dialysate were tested: dialysate 1, acetate-free with 1mmol/L of citrate; dialysate 2, with 0.8mmol/L of citrate and 0.3mmol/L of acetate; dialysate 3, citrate-free with 3mmol/L of acetate; and dialysate 4, citrate-free with 4mmol/L of acetate. The cell types used were: human monocyte culture (THP-1); and peripheral blood mononuclear cells (PBMCs) from healthy subjects and uraemic patients on haemodialysis. ICAM-1 was determined and levels of reactive oxygen species and total microvesicles were quantified. Unlike the citrate dialysates, the dialysates with acetate (dialysate 3 and dialysate 4) induced increased ICAM-1 expression density in THP-1 cells; an increase in ICAM-1 expression was observed in the immunocompetent cells of healthy subjects with acetate dialysate (dialysate 3 and dialysate 4) but not with citrate dialysate (dialysate 1 and dialysate 2). No significant ICAM-1 differences were found between the different dialysates in the cells of haemodialysed patients. Reactive oxygen species expression and the number of microvesicles increased significantly with acetate dialysate but not with citrate dialysate in the cells of both healthy subjects and haemodialysed patients. At the concentrations in which it is generally used in clinical practice, acetate-based dialysate increases oxidative stress and the total number of microvesicles and may induce other pro-inflammatory stimuli typical of uraemic patients on haemodialysis. Citrate dialysates do not induce this activation, which could make them a suitable alternative in clinical practice.